Closed-loop process for recovery of metals from NdFeB magnets using a trichloride ionic liquid - Li, Xiaohua; Li, Zheng; Binnemans, Koen (Separation and purification technology, 2021)
Synopsis: Rare-earth metals and cobalt can be recovered from spent NdFeB magnets using an oxidative ionic liquid which can be reused in next cycles. [Display omitted] •NdFeB magnets can completely dissolve in a trichloride ionic liquid.•Elements in NdFeB magnets are oxidized by trichloride ionic liquids.•Rare-earth and transition metals can be removed selectively by two stripping steps.•Trichloride ionic liquid can be recycled and reused for dissolution of magnets. A solvometallurgical process was developed to recover rare-earth elements and cobalt from end-of-life NdFeB magnets, using the ionic liquid (IL) trihexyltetradecylphosphonium trichloride ([P666,14][Cl3]), or a mixture of [P666,14][Cl3] and the corresponding chloride IL [P666,14]Cl. The process comprises dissolution, stripping and regeneration of the ionic liquid. Pure [P666,14][Cl3] or its mixture with [P666,14]Cl could quantitatively dissolve NdFeB magnets when the solid-to-liquid ratio was less than a certain threshold value that depended on the volume percentage of [P666,14][Cl3] in the lixiviant. Increasing the temperature from 25 to 50 °C enhanced the dissolution rate significantly, but the dissolution efficiency increased only marginally. The volume percentage of [P666,14][Cl3] in [P666,14]Cl had a positive effect on the dissolution efficiency. The rare-earth and transition metals could be removed selectively by two sequential stripping steps, using 3 mol∙L−1 of NaCl aqueous solution and >2 mol∙L−1 of aqueous ammonia solutions, respectively. The regenerated IL [P666,14][Cl3] showed a similar dissolution efficiency to the fresh ionic liquid.